2011
DOI: 10.1152/ajpgi.00482.2010
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress exacerbates murine colitis by enhancing proinflammatory cytokine expression that is dependent on IL-18

Abstract: Psychological stress is an environmental factor considered to be a precipitating factor of inflammatory bowel disease. Interleukin (IL)-18 plays a role in stress-induced aggravation in some diseases. The aim of this study was to establish a model of murine colitis exacerbated by psychological stress and to clarify the role of IL-18 in this model. Male C57Bl/6 mice and IL-18(-/-) mice were used for this study. The mice received dextran sulfate sodium (DSS) for induction of colitis. Some mice were exposed to psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Moreover, Matsunaga et al . () also found that IL‐18 was involved in the pathophysiology of the proinflammatory response in colonic inflammation under psychologically stressful conditions, using IL‐18 knockout mice and an anti‐IL‐18 antibody. Furthermore, Verri et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, Matsunaga et al . () also found that IL‐18 was involved in the pathophysiology of the proinflammatory response in colonic inflammation under psychologically stressful conditions, using IL‐18 knockout mice and an anti‐IL‐18 antibody. Furthermore, Verri et al .…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have contributed to the current state of knowledge regarding the role of IL‐18 in tissue injury (Verri et al ., ; Matsunaga et al ., ; Wyburn et al ., ). Wyburn et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidirectional functional consequences of neuro-immune interactions have been appreciated for decades (Besedovsky et al, 1983; Stead et al, 1987), with emphasis given to stress-mediated alterations in immune responses and, conversely, cytokine-mediated alterations in CNS including animal behavior and brain activity (Matsunaga et al, 2011; Serrats et al, 2010). As an example, efferent vagal nerve signals were shown to attenuate macrophage activity leading to anti-inflammatory responses in the intestine (de Jonge et al, 2005; Rosas-Ballina et al, 2011; Wang et al, 2003).…”
Section: Neuro-immune Interactions In Health and Diseasementioning
confidence: 99%
“…Interleukin-18 (IL-18) is a pro-inflammatory cytokine which has been linked with varying degrees of evidence to diseases as diverse as cardiovascular disease (Jefferis et al, 2011), asthma (Ma et al, 2012), inflammatory bowel disease (Siegmund, 2010; Matsunaga et al, 2011; Rivas et al, 2011), acute kidney injury (Ho, Fard & Maisel, 2010), and type 1 (Smyth et al, 2008) and type 2 diabetes (Thorand et al, 2005; Hivert et al, 2009), either through associations with IL-18 itself or with its receptor or binding protein. The IL-18 receptor belongs to the interleukin-1/Toll-like receptor superfamily, and is encoded by two genes— IL18R1 and IL18RAP —which encode a ligand-binding subunit (commonly known as IL-18R α ) and accessory protein (IL-18R β ) subunit, respectively (Dinarello, 2009).…”
Section: Introductionmentioning
confidence: 99%